PENGARUH ORGANIZATIONAL ETHICS TERHADAP JOB SATISFACTION PADA BANK-BANK SWASTA DI JAKARTA - Zainul Bahri Dalimunthe (Media Riset Bisnis & Manajemen, 2005)
The influence of organizational ethics toward job satisfaction with Standardized Beta (à) is very high (= 0,856) and Adjusted R? = 0.732 and significant at level of significance 5%. It represents, that the contribution of organizational ethics toward job satisfaction on the private banks is 73,2 %. Among the three dimensions which form organizational ethics, the organization's ethical climate (â= 0,429) appears to be the biggest influence and the association between ethical behavior and career success (â= 0,376); and top management support for ethical behavior (a= 0,113) as the lowest influence.The managerial implication from this research is that the private banks' managers can give the more attention to every dimension above. Advises for the future researchers is to do another research that related to the human resource development, such as the link between job satisfaction and organizational commitment.